Badan Hukum Penanaman Modal Asing dalam Undang-Undang Nomor 40 Tahun 2007 tentang Perseroan Terbatas - Lu Sudirman (Fakultas Hukum, Universitas Internasional Batam, 2016)
Law concerning Limited Liability Company does not distinguish any foreign investment or planting of the Interior as well as local companies. All the requirements set forth in the Company Law applies equally to all types of companies. The difference between domestic and foreign, as well as companies contained in the rules of Investment Law No. 25 of 2007 which gives the requirements that must be met for foreign investment and domestic investment.The main characteristic of Limited Liability is that Limited Company is a subject to legal status of a legal entity, which in turn makes limited liability responsible for shareholders, members of the Board of Directors, and Commissioners. However, keeping up with the development of the business world so rapidly only make companies are too focused on the economic and productive activities only, so they forgot about the situation in around the operation area.The issue of social responsibility is a topic which related to business ethics, in this case there is the moral responsibility of companies not only for employees of companies but also people around the company. The strategic role of social responsibility (CSR) in Indonesia has been regulated in the Law on Limited Liability Companies. One of the booster of CSR developments that occurred in Indonesia is a paradigm shift in the business world that is not solely for profit, but also behave ethically and contribute to the creation of a social investment.